2009
DOI: 10.1111/j.1439-0310.2009.01707.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental and Mating Effort: Is There Necessarily a Trade‐Off?

Abstract: One of the common assumptions in the study of the evolution of parental care is that trade‐offs exist between parental investment and other fitness‐related traits. In general, this body of work follows the traditional definition that parental investment (in the current offspring) decreases that individual’s ability to invest in future reproduction (Trivers 1972). However, examination of the empirical evidence shows that assuming a trade‐off between parental and mating effort is not always appropriate. This ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
133
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 217 publications
(256 reference statements)
4
133
0
Order By: Relevance
“…However, if successful provisioning depends on the control of resources through physical competition, high ASRs might be associated with violence. Much of the logic above assumes a tradeoff between parenting effort and mating effort, which is not always the case [96]. In some species, providing parental care can be a key element of the mate competition strategy of a male, as in two-spotted goby (Gobiusculus flavescens) [33].…”
Section: Additional Complicating Factorsmentioning
confidence: 99%
“…However, if successful provisioning depends on the control of resources through physical competition, high ASRs might be associated with violence. Much of the logic above assumes a tradeoff between parenting effort and mating effort, which is not always the case [96]. In some species, providing parental care can be a key element of the mate competition strategy of a male, as in two-spotted goby (Gobiusculus flavescens) [33].…”
Section: Additional Complicating Factorsmentioning
confidence: 99%
“…Increased fecundity could also be favoured when paternal care increases at greater clutch sizes [25,26]. However, these are largely qualitative post-hoc explanations of reproductive compensation [4], and therefore are somewhat unsatisfactory. A related problem is that male and female condition or age can affect offspring size and number [27,28], which can cloud one's ability to detect differential allocation and compensation [29].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews of empirical studies of mating and reproductive investment [4,18] found evidence for both differential allocation and reproductive compensation in a wide range of taxa, including insects, fish, amphibians and birds. Evidence of differential allocation and compensation included several different response metrics, such as differential offspring survival and growth, egg size, clutch size and androgen levels (see e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations